An Analysis of the Responsibility to Protect Program in Light of the Conflict in Syria - Michael Small (Washington University Global Studies Law Review, 2014)
Following numerous humanitarian brutalities committed throughout the 1990s around the world, the United Nations sought to create a protocol that would allow the international community to prevent further mass atrocity crimes. After many debates and compromises, the Responsibility to Protect program was created. Consisting of three ideological “pillars,” the protocol allows other nations to interfere if a country is committing one of four mass atrocity crimes against its own populace. Such interference can range from an official reprimand to military intervention. This program has already been employed in Libya and the Côte d’Ivoire; however, its lack of use in the ongoing Syrian conflict speaks to a level of deficiency in the program itself. While members of the international community have had varying criticisms of the program, the Responsibility to Protect program suffers most from the political realities and strategic alliances that permeate the United Nations Security Council. Although several reforms of the Responsibility to Protect have been suggested, ranging from adopting national programs to political compromise, no reform seems imminent. It appears that this groundbreaking program is here to stay—for better or for worse.
Keywords: United Nations; responsibility to protect; crimes against humanity; mass atrocities; international intervention; Security Council